Evaluating STAT5 Phosphorylation as a Mean to Assess T Cell Proliferation - Bitar, Michael; Boldt, Andreas; Freitag, Marie-Theres; Gruhn, Bernd; Köhl, Ulrike; Sack, Ulrich (Frontiers in Immunology, 2019)
Here we present a simple and sensitive flow cytometric – based assay to assess T cell proliferation. Given the critical role STAT5A phosphorylation in T cell proliferation, we decided to evaluate phosphorylation of STAT5A as an indicator of T cell proliferation. We determined pSTAT5A in T cell treated with either CD3/CD28 or PHA. After stimulation, T cells displayed a strong long-lasting phosphorylation of STAT5A, reaching a peak value after 24 hours. The median fluorescence intensity (MFI) of pSTAT5A increased from 112 ± 17 to 512 ± 278 (CD3/CD28) (24 h) and to 413 ± 123 (PHA) (24 h), the IL-2 receptor-α (CD25) expression was greatly enhanced and after 72 h T cell proliferation amounted to 52.3 ± 10.3 % (CD3/CD28) and to 48.4 ± 9.7 % (PHA). Treatment with specific JAK3 and STAT5 inhibitors resulted in a complete blockage of phosphorylation of STAT5A, CD25 expression, and suppression of T cell proliferation. Compared with currently available methods, STAT5A phosphorylation is well suited to predict T cell proliferation. Moreover, the method presented here is not very time consuming (several hours) and delivers functional information from which conclusions about T cell proliferation can be drawn.